Macroeconomics - Colander, David C. (New York: McGraw hill, 2024)
"The goal of this macro edition is to convey to students the ideas that make up modern economics. The ideas are both about the way the economy works, and about how to design policy to make the economy work better"--
Includes index.
Keywords: Macroeconomics